The school of essential ingredients - Bauermeister, Erica (G. P. Putnam's Sons, 2009)
Eight students gather in Lillian's Restaurant every Monday night for cooking class. It soon becomes clear, however, that each one seeks a recipe for something beyond the kitchen as Chef Lillian, a woman whose connection with food is both soulful and exacting, helps them to create dishes whose flavor and techniques expand beyond the restaurant and into the secret corners of her students' lives.